1998
DOI: 10.1210/jcem.83.7.4964
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Insulin Growth Factor-I (IGF-I) and a Simple Sequence Repeat in IGF-I Gene: Implications for Genetic Studies of Bone Mineral Density

Abstract: We recently demonstrated that insulin growth factor-I (IGF-I) cosegregates with bone mineral density (BMD) in progenitor crosses of two inbred strains of mice. Additionally, we reported that men with idiopathic osteoporosis (IOM) have low serum IGF-I levels, which can be related to BMD and bone turnover. In this study, we considered the possibility that serum IGF-I levels are influenced by molecular genetic variation in the IGF-I structural gene, and that a polymorphic microsatellite (CA repeat) in this locus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
90
1
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(108 citation statements)
references
References 18 publications
11
90
1
6
Order By: Relevance
“…Twin studies (Kao et al, 1994;Harrela et al, 1996) have shown that about 50% of the inter-individual variability in circulating IGF-1 levels is genetically determined. The IGF1 polymorphism is located in the promoter region of the IGF1 gene (Rosen et al, 1998). This microsatellite polymorphism is located one kilobase upstream from the IGF1 transcription start site (Rotwein et al, 1986;Weber and May, 1989) and contains specific regulatory elements (McCarthy et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twin studies (Kao et al, 1994;Harrela et al, 1996) have shown that about 50% of the inter-individual variability in circulating IGF-1 levels is genetically determined. The IGF1 polymorphism is located in the promoter region of the IGF1 gene (Rosen et al, 1998). This microsatellite polymorphism is located one kilobase upstream from the IGF1 transcription start site (Rotwein et al, 1986;Weber and May, 1989) and contains specific regulatory elements (McCarthy et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The promoter region of the IGF1 gene contains a CA-repeat sequence, which ranges from 12 to 23 repeats (Rosen et al, 1998). Most white women have at least one copy of the 19-repeat allele (Jernström et al, 2001b), but the frequency of the 19-repeat allele varies between ethnic groups (Jernström et al, 2001a).…”
mentioning
confidence: 99%
“…We performed PCR amplification of the DNA region surrounding the microsatellite repeat in question using identical primers to those used in the study by Rosen et al (1998). Their sequences were as follows 5 0 GCTAGCCAGCTGGTGGTGTTATT3 0 and 3 0 ACCACTCTGGGAGAAGGGTA5 0 .…”
Section: Igf1 (Ca) N Genotypingmentioning
confidence: 99%
“…We extracted DNA from the buffy coats of peripheral blood samples using the Puregene genomic DNA isolation kit (Gentra Systems, Minneapolis, MN, USA). We used a modified genotyping protocol as described by Rosen et al (1998). A total of 20 ng of DNA template, 1.25 pmols of each primer, 0.25 mM of each deoxynucleotide triphosphate, 2.5 mM MgCl 2 , 2% dimethyl sulphoxide, 1.5 U Taq polymerase (Promega, Madison, WI, USA) and the manufacturer's recommended buffers were combined in 25 ml reactions.…”
Section: Igf1 (Ca) N Genotypingmentioning
confidence: 99%
“…The IGF1 gene contains a dinucleotide cytosine-adenine (CA) repeat in the proximity of the promoter, 1kb upstream from the transcription start site (Weber & May, 1989). The CA repeat sequence ranges from 11 to 24 repeats (Rosen et al, 1998;Schildkraut et al, 2005).…”
mentioning
confidence: 99%